PENGARUH KUALITAS UDARA AMBIEN TERHADAP KELUHAN SUBJEKTIF GANGGUAN PERNAPASAN SEBAGAI BAHAN KEBIJAKAN PENGELOLAAN LINGKUNGAN HIDUP - Amirullah, Arul; Muhlisin, Muhlisin; Akbari, Tauny (Jurnal Kebijakan Pembangunan Daerah, 2023)
Transportation activities at Kadu Agung Mandala Terminal have the potential to emit harmful substances that affect the respiratory health of terminal users. Therefore, there is a need for a policy to control ambient air quality to mitigate its impact on respiratory issues among terminal users. This study aims to analyze ambient air quality (SO2 and NO2), assess the level of subjective complaints related to respiratory disorders, and investigate the effects of ambient air quality on these complaints. The research employed a quantitative descriptive method, with the study population comprising terminal users. Purposive sampling was used to select 45 respondents, and measurements of ambient air quality (SO2 and NO2) were taken at three locations within the terminal. The study's results indicate that the ambient air quality parameters for SO2 (23.1 µg/Nm3) and NO2 (14.17 µg/Nm3) are still within acceptable standards. However, despite pollutant concentrations being below the quality standard, 77.1% or 34 individuals reported subjective complaints related to respiratory problems. Notably, the concentration of SO2 at 23.1 µg/m3 is associated with throat irritation, eye irritation, and coughing, while NO2 at 14.17 µg/m3 leads to throat irritation and coughing. Ambient Air Quality Control Policy is carried out by monitoring ambient air quality and carbon gas emissions, expanding the area of green open space and supervising the driving test and spot check of motorized vehicles to meet exhaust emission standards.